'Detour coiffure': Veronica Lake and her peekaboo hairstyle. Issue 1 (2nd January 2016) - Phullar, Kulraj
Abstract : Veronica Lake became – and remains – most famous for her iconic blond peekaboo hairstyle. This article examines the promotion, representation and reception of the hairstyle during the early years of Lake's career. It considers her emergence as a star and breakthrough performance in the aviation drama I Wanted Wings . As the tragic femme fatale Sally Vaughn, Lake established a star image as a glamorous and hardboiled modern vamp. The second half of the article attempts to gauge the popularity and cultural currency of Lake's blond peekaboo hairstyle across a range of extra-filmic texts, including magazine features, jokes, animations and other films. Scrutinising representational strategies in these texts enables an understanding of Lake's status as a celebrity, sex symbol and fashion icon. The article concludes by discussing the implications of Lake's star image and media visibility for film noir, arguing that she was its first female star and an important influence on subsequent performers.